(untitled) (Bangladesh Critical Care Journal, 2022)
Background: Intubation and mechanical ventilation are integral parts of critical care management. Though a lifesaving intervention, invasive mechanical ventilation imposes a great risk of nosocomial pneumonia to the patient. Ventilator associated pneumonia rates in an ICU is a predictor of successful infection control strategy. Objectives: objective of the current study was to study the frequency of ventilator associated pneumonia and its outcome in the critical care setting. Methods: This prospective observational cross-sectional study was done in department of critical care medicine of BIRDEM General Hospital for the period of 1st July, 2017 to 30th June, 2018. All consecutive patients who were intubated and mechanically ventilated for a period of at least 48 hours within the study period were evaluated for the selection criteria of the study. The included study participants were followed up daily for signs of development of VAP. Once VAP was suspected pertinent investigations were sent to confirm the diagnosis. Study participants were observed regularly to identify signs of pulmonary infection. The microbiological tests were done in the Department of Microbiology of BIRDEM. Quantitative culture was done (expressed as CFU/ml) and antibiotic sensitivity was done by standard disc diffusion method. A cutoff value of 105 CFU/ml was taken as a positive culture. CPIS score was calculated to diagnose VAP .The study participants were followed up to transfer to step down unit/ward or death to see the outcome. Data were collected in preformed data collection sheet and analyzed by the statistical packages for social sciences (SPSS) software version 22. Results: In this study total 92 patients out of 625 intubated patients during the study period after fulfilling the inclusion criteria were selected as study participants. The mean age of the the participants who developed VAP was 65.05±14.79 years with a range of 27 to 101 years. 62.9% (n=22) were female and 37.1% (n=13) were male. In this study DM, HTN & Renal disease were the most common co-morbidities. Among the 35 VAP positive participants 51.4% (n=18) developed early onset VAP and 48.6% (n=17) developed late onset VAP. Among the VAP positive participants 31.4% were survivors and 68.6% were non-survivors and among the VAP negative participants 68.4% were survivors and 31.6% were non survivors (p=0.001). Conclusion: Frequency of VAP was 5.6% in the study. It was associated with significantly prolonged length of mechanical ventilation and length of ICU stay and high mortality. Bangladesh Crit Care J March 2022; 10 (1): 43-47